Image Learning of Electric Characteristics of Resistance, Capacitance, Inductance, and their Circuits by Java Programming - Morooka, Masami; Qian, Suhua; Morooka, Midori (Transactions on Engineering and Computing Sciences, 2014)
Java programs with a graphical user interface (GUI) environment have been developed for an image learning of electric characteristics of resistance (R), capacitance (C), inductance (L), and their circuits. Text fields of selected parameters for the numerical calculation of the differential equations to describe the electric characteristics of the circuit are set on the display, such as the frequency of applied voltage and the values of R, C, L, time increments, and calculation times. The calculation used Runge-Kutta method is initiated by clicking the start button after inputting the desired values into the text fields. The calculated results are plotted immediately after the completion of the calculation as a figure on the display for the simulation of the electric characteristics of the circuit, such as changes in the voltages and currents with time. By changing the values in the text fields, the new results are represented immediately, and the new electric characteristics of the new circuit can be easily simulated. These Java programs are useful in education applications for rapidly and accurately image learning for the electric characteristics of the circuit. This program is also useful for learning the phenomena expressed by ordinary differential equations.